1981
DOI: 10.1071/ch9812505
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of coordination compounds. XII. N- and C-Substituted five-membered diamine chelate rings

Abstract: An analysis of the 3JH,H coupling constants for the CH2CH2 segment in the chelate rings formed by N-methylethane-1,2-diamine, and a crystal structure analysis of [Co(NH3)4{(±)-pn}] (S2O6)1.5,H2 (pn, propane-1,2-diamine) have shown that in cobalt(III) five-membered diamine chelate rings the NCCN torsional angle is approximately 51°. For platinum(II) complexes of N-methylethane-1,2- diamine, the 3JH,H technique yielded a value of 52.5° for the NCCN torsional angle. Problems involved with the refinement of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…~~' ~, ' * It has been reported that protons in the CHCH,CH fragment of the 2R,4R-ptn chelate are observed as a A,B2 pattern even for the case in which the contribution of the skew-boat conformation is dominant, although an AA'BB' pattern is expected for this conformation. 18 The present complexes also show an A,B, pattern for these protons. The JAB value is 8.3 Hz for l b and 6.4 Hz for la, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…~~' ~, ' * It has been reported that protons in the CHCH,CH fragment of the 2R,4R-ptn chelate are observed as a A,B2 pattern even for the case in which the contribution of the skew-boat conformation is dominant, although an AA'BB' pattern is expected for this conformation. 18 The present complexes also show an A,B, pattern for these protons. The JAB value is 8.3 Hz for l b and 6.4 Hz for la, respectively.…”
Section: Discussionsupporting
confidence: 63%
“…A Karplus analysis , of the vicinal proton−proton coupling constants within the NCH 2 CH 2 N‘ multiplets of 1 indicates that N,N‘-chelate binding to Li results in a five-membered chelate ring with predominantly (94.2%) λ-conformation (Figure ). The calculated torsion angle (ω) is 58.2°.…”
Section: Resultsmentioning
confidence: 99%
“…Several approximations for complexes of transition-metal ions, predominantly in "bonded" MM models that include electron distribution effects, are accordingly found; these range from setting the M-L dipoles to zero and excluding charges to arbitrary choices of parameters. 52,[56][57][58][59]61,[64][65][66][67][68]86 Electrostatic parameters for metalligand interactions will obviously be more critical in the "nonbonded" approach,62 and a recent strategy, in which dynamic adjustment of charge distribution in the M-L bonds during conformational optimization is effected, has improved the reliability of calculations for metal ions in proteins.62 However, it is interesting to note that in several instances there are only minor differences in the results, arising from small variations in, or the neglect of, electrostatic parameters.87-89…”
Section: Sad Sadmentioning
confidence: 99%